Another Bloody Clean-Up: The Experiences of Trauma Cleaners in South Africa - David Du Toit and Buck Whaley (University of Johannesburg, 2021)
South Africa has one of the highest violent crime rates globally, where physical and emotional trauma is used in homicides and suicides. While this is apparent to the ordinary South African, what is less clear is what happens after the police and forensics have done their job at a crime scene: Who cleans up the bloody mess? In South Africa, as in many other nations, trauma cleaners restore the scenes where homicides and suicides have been committed, and where industrial accidents have taken place. Little to no scholarly research has been conducted on the experiences of the cleaners of trauma scenes. Cleaning up these scenes consists of labour charged with violence that most cannot countenance, but which the cleaner must face. Drawing on 13 qualitative interviews, this article explores the challenges of cleaning up a site where violent and/or traumatic acts have occurred, and how the cleaners develop strategies to cope with their own concomitant trauma. The cleaners are exposed to various health and safety issues, as well as the emotional trauma associated with cleaning up horrific accidents and crimes. Findings show that trauma cleaners emotionally distance themselves from the violence to which they bear witness and use emotional labour, spirituality, humour, and debriefing as coping strategies. In its conclusion, this article suggests a greater acknowledgement of trauma cleaners’ responsibilities and recommends that proper physical and emotional training is necessary to ensure their wellbeing.